2011
DOI: 10.3109/14659891.2011.580414
|View full text |Cite
|
Sign up to set email alerts
|

Food service employee alcohol use, hangovers and norms during and after work hours

Abstract: Aims This paper presents analyses of norms and behavior concerning drinking before, during, and after work hours among U.S. bar-restaurant chain employees, with a focus on hangovers at work and their correlates. Methods A mixed method approach combined qualitative analysis of 64 face-to-face interviews held with randomly chosen service, managerial and kitchen staff and quantitative analyses (including multivariable linear regression and bivariate analyses) of data drawn from 1,286 completed telephone surveys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Employees' alcohol consumption also contributes to absenteeism (Bacharach et al, 2010;Holden et al, 2011;Jauregui and Schnall, 2009;Klingemann and Gmel, 2001;Pidd et al, 2006;Roche et al, 2008), reduced functioning (Ames et al, 1997;Holden et al, 2011;Mangione et al, 1999;Moore et al, 2012), disharmonious working relationships (Ames et al, 1997;Lehman and Simpson, 1992;Wang et al, 2010), employee turnover (Hoffmann and Larison, 1999), loss of productivity, and financial costs to employers (European Commission, 2011). High risk drinkers are approximately 22 times more likely to be absent from work due to their alcohol use compared to low risk drinkers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Employees' alcohol consumption also contributes to absenteeism (Bacharach et al, 2010;Holden et al, 2011;Jauregui and Schnall, 2009;Klingemann and Gmel, 2001;Pidd et al, 2006;Roche et al, 2008), reduced functioning (Ames et al, 1997;Holden et al, 2011;Mangione et al, 1999;Moore et al, 2012), disharmonious working relationships (Ames et al, 1997;Lehman and Simpson, 1992;Wang et al, 2010), employee turnover (Hoffmann and Larison, 1999), loss of productivity, and financial costs to employers (European Commission, 2011). High risk drinkers are approximately 22 times more likely to be absent from work due to their alcohol use compared to low risk drinkers .…”
Section: Introductionmentioning
confidence: 99%
“…High risk drinkers are approximately 22 times more likely to be absent from work due to their alcohol use compared to low risk drinkers . Workplace performance may also be impaired by presenteeism (Ames et al, 1997;Aronsson et al, 2000;Moore et al, 2012). Costs arising from presenteeism are estimated to be four times higher than that of absenteeism (Manning et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2,10 There is a significant financial cost to employers through alcohol's association with accidents, mortality, and injury, [11][12][13][14][15] and employee alcohol consumption has been associated with absenteeism and lower than optimum functioning at work (''presenteeism'') and reduced productivity and workplace turnover. 14,[16][17][18] High-risk drinkers are up to 22 times more likely to be absent from work because of their alcohol use compared with low-risk drinkers 18 ; costs arising from presenteeism are estimated to be four times higher than that of absenteeism. 8 Other factors that have been associated with alcohol and the workplace include the type and quality of work being performed, isolation, low levels of supervision, the availability of alcohol at or after work, norms surrounding drinking, and peer approval of drinking at work.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol use outside work was common. One study found 85.5% of 1294 respondents reported drinking after work and 36.5% of employees reported coming to work hungover 75 . Excessive drinking is normalized in restaurant culture and alcohol's ready availability has been shown to influence consumption and lead to problematic usage.…”
Section: Occupational Health In Restaurant Workmentioning
confidence: 99%